2011
DOI: 10.1088/0022-3727/44/16/165407
|View full text |Cite
|
Sign up to set email alerts
|

PST thin films for electrocaloric coolers

Abstract: Relaxor behaviour in a thin film of partially ordered PbSc 0.5 Ta 0.5 O 3 (PST) was confirmed via slim P-E loops and the frequency dependence of the temperature at which the dielectric constant is maximum. Indirect measurements of the electrocaloric effect suggest that removing a field of 774 kV cm-1 yields a temperature change of-3.5ºC to-6.9ºC over a broad range of operating temperatures near room temperature (1 ºC-127 ºC), with a correspondingly large refrigerant capacity of 662 J kg-1. In addition to low e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 19 publications
2
67
1
Order By: Relevance
“…Under an ultrahigh field of 800 kV/cm, the sample exhibits a giant electrocaloric effect of DT ¼ 7.1 K and DS ¼ 10.1 J/kg Á K at 80 C, 15 which exceeds the ECE value in most ferroelectric ceramics in previous reports. [5][6][7][8][9][10] Although the PbZr 0.95 Ti 0.05 O 3 thin film in Ref. 3 has higher ECE DT of $12 C, its DS of $8 J/kg Á K is smaller due to high operating temperature of 222 C. Because (1) large entropy change is more practical for the refrigerating application, (2) low working temperature would open up wider application prospect, and (3) large effective volume of multilayer thick film produces huger heat absorption capacity, the BaTiO 3 multilayer thick film has more promising application future.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under an ultrahigh field of 800 kV/cm, the sample exhibits a giant electrocaloric effect of DT ¼ 7.1 K and DS ¼ 10.1 J/kg Á K at 80 C, 15 which exceeds the ECE value in most ferroelectric ceramics in previous reports. [5][6][7][8][9][10] Although the PbZr 0.95 Ti 0.05 O 3 thin film in Ref. 3 has higher ECE DT of $12 C, its DS of $8 J/kg Á K is smaller due to high operating temperature of 222 C. Because (1) large entropy change is more practical for the refrigerating application, (2) low working temperature would open up wider application prospect, and (3) large effective volume of multilayer thick film produces huger heat absorption capacity, the BaTiO 3 multilayer thick film has more promising application future.…”
Section: Resultsmentioning
confidence: 99%
“…Since 2006, the giant ECE (DT max > 5 K) was reported successively in various ferroelectric ceramics or polymer films, [3][4][5][6][7][8][9][10][11][12] where the ultrahigh applied field played a key role. Up to now, intense research and development efforts are still on-going and there are many blank, especially on the kinetics problem.…”
Section: Introductionmentioning
confidence: 99%
“…Although ECE research has been carried out for several decades, 1-3 the underlying physics behind ECE and its relation with phase transition are not yet completely understood. The thermodynamic theory based on the Maxwell relation was widely used in the characterization and analysis of ECE, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] but recent reports revealed that it is unsuitable for ferroelectric relaxors with non-ergodic glassy state 11,12 and becomes invalid near phase transitions 5,12 or under ultrahigh electric field, 14 which are two keys to achieve giant ECE. Since the origination of giant ECE has not been properly interpreted, the development of highly-efficient ferroelectric refrigeration is put off.…”
Section: Aip Advances 2 022162 (2012)mentioning
confidence: 99%
“…[1][2][3][4][5] Since 2006, a giant ECE with T = 5∼40K was subsequently observed in ferroelectric films under ultrahigh electric fields. [6][7][8][9][10][11][12][13][14] Although ECE T and/or S of thin films under high fields is much higher than that of bulk samples, the effect under unit field is weakened significantly, 4 about one order of magnitude (from 0.2∼1.0K · m/MV to 0.01∼0.1K · m/MV). In this paper, we quantitatively distinguish the dominant factor of ECE near a phase transition, and achieve a large effect of T/E = 1.4K · m/MV in BaTiO 3 near room temperature (RT).…”
Section: Aip Advances 2 022162 (2012)mentioning
confidence: 99%
See 1 more Smart Citation